RELATIONSHIP BETWEEN BOARD INDEPENDENCE AND CSR SPENDING OF ISLAMIC BANKS IN BANGLADESH - Umar, Umar Habibu (Journal of Islamic Monetary Economics and Finance, 2022)
This study examines the relationship between board independence and CSR expenditures on education, health and human and disaster relief for the case of Islamic banks in Bangladesh, Using unbalanced panel data from 2010 to 2020, the results indicate that board independence is positively and significantly associated with CSR expenditures on education and human and disaster relief sectors but is insignificantly related to the CSR expenditure on health. Thus, in forming the governance framework of Islamic banks, there is a need to have board independence to promote the social responsibility of Islamic banks.  Indeed, our results suggest that it should be a regulatory requirement.